A Novel Multi-Modal Network-Based Dynamic Scene Understanding - Uddin, Md Azher; Joolee, Joolekha Bibi; Lee, Young Koo; Sohn, Kyung Ah (ACM Transactions on Multimedia Computing, Communications and Applications, 2022)
In recent years, dynamic scene understanding has gained attention from researchers because of its widespread applications. The main important factor in successfully understanding the dynamic scenes lies in jointly representing the appearance and motion features to obtain an informative description. Numerous methods have been introduced to solve dynamic scene recognition problem, nevertheless, a few concerns still need to be investigated. In this article, we introduce a novel multi-modal network for dynamic scene understanding from video data, which captures both spatial appearance and temporal dynamics effectively. Furthermore, two-level joint tuning layers are proposed to integrate the global and local spatial features as well as spatial and temporal stream deep features. In order to extract the temporal information, we present a novel dynamic descriptor, namely, Volume Symmetric Gradient Local Graph Structure (VSGLGS), which generates temporal feature maps similar to optical flow maps. However, this approach overcomes the issues of optical flow maps. Additionally, Volume Local Directional Transition Pattern (VLDTP) based handcrafted spatiotemporal feature descriptor is also introduced, which extracts the directional information through exploiting edge responses. Lastly, a stacked Bidirectional Long Short-Term Memory (Bi-LSTM) network along with a temporal mixed pooling scheme is designed to achieve the dynamic information without noise interference. The extensive experimental investigation proves that the proposed multi-modal network outperforms most of the state-of-The-Art approaches for dynamic scene understanding.
Keywords: Dynamic scenes; Graph structures; Memory network; Multimodal network; Stacked bidirectional long short-term memory network; Symmetrics; Temporal mixed pooling; Transition patterns; Volume local directional transition pattern; Volume symmetric gradient local graph structure; Multi-modal network; stacked Bi-LSTM network; temporal mixed pooling; volume local directional transition pattern; volume symmetric gradient local graph structure